IDEOLOGY CONSTRUCTION AND ITS SIGNIFICATION A SOCIO-COGNITIVE ANALYSIS OF BOB MARLEY'S SELECTED LYRICS - Kusumah, Wildhan Akbar (2016)
This paper entitled Ideology Construction and Its Signification A Socio-Cognitive Analysis of the Selected Bob Marley's Song lyrics aims to uncover the ideology constructed within Bob Marley's selected lyrics and its signification. This study uses a qualitative descriptive method. Van Dijk's (2009) Socio-Cognitive Approach is utilized as framework in this study. The results of this study show that Rastafari ideology is constructed within the analyzed lyrics. It is identified through the occurrence of its value within the topic selection which is supported by the use of metaphor and narrator shifting. The occurrence of ideology within the lyric indicates the ideology the writer brings is based on the awareness of social problem, especially social injustice issue. Keywords: Song Lyrics, Bob Marley, Van Dijk's Socio-Cognitive Approach, Metaphor, Narrator Shifting Penelitian yang berjudul "Ideology Construction and Its Signification: A Socio-Cognitive Analysis of the Selected Bob Marley's Lyrics" bertujuan untuk menelusuri pembembentukkan ideologi di dalam lirik lirik lagu Bob Marley yang terpilih dengan menggunakan metode penelitian deskriptif kualitatif. Pendekatan Socio-Cognitive dari Van Dijk (2009) digunakan sebagai kerangka penelitian disini. Hasil penelitian menunjukkan bahwa ideology Rastafari terbentuk pada lirik dengan cara penggunaan topik yang didukung pula dengan metafora dan perubahan penyampai. Ideologi yang terdapat pada lirik-lirik lagu Bob Marley menunjukkan kesadaran penulis akan masalah social terutama isu mengenai ketidakadilan sosial. Kata kunci: Lirik lagu, Bob Marley, Pendekatan Socio-Congitive Van Dijk, Metafora, Perubahan penyampai.